The Stereoselective Nitro-Mannich Reaction in the Synthesis of Active Pharmaceutical Ingredients and Other Biologically Active Compounds - Faisca Phillips, Ana Maria; Guedes da Silva, M. Fátima C.; Pombeiro, Armando J. L. (Frontiers in Chemistry, 2020)
The nitro-Mannich (aza-Henry) reaction, in which a nitroalkane and an imine react to form a β-nitroamine, is a versatile tool for target-oriented synthesis. Although the first stereoselective reaction was developed only 20 years ago, and enantioselective and diastereoselective versions for the synthesis of non-racemic compounds soon after, there are nowadays a variety of reliable methods which can be used for the synthesis of APIs and other biologically active substances. Hence many anticancer drugs, antivirals, antimicrobials, enzyme inhibitors and many more substances, containing C–N bonds, have been synthesized using this reaction. Several transition metal complexes and organocatalysts were shown to be compatible with the presence of a wide range of functional groups in these molecules, and very high levels of asymmetric induction have been achieved in some cases. The reaction has also been applied in cascade processes. The structural diversity of the products, ranging from simple heterocycles or azabicycles to complex alkaloids, iminosugars, amino acids or diamino acids and phosphonates, shows the versatility of the nitro-Mannich reaction and its potential for future developments.